Externalizing Behaviors of Children as Predicted by Maternal Psychological Well-being - Roy, Kishor; Muhammad, Noor (Jagannath University Journal of Science, 2024)
Most of the behaviors of children depend on their parents’ psychological well-being. This study investigated the relationship of maternal psychological well-being with externalizing behaviors of children. A Personal Information Form (PIF), an adapted self-reported Bangla version of the Strengths and Difficulties Questionnaire (SDQ), and an adapted General Health Questionnaire (GHQ-28) were administered on 800 (400 children, 400 mothers) participants to collect data. The children were selected from ten Bangla medium high schools in Dhaka city and their age ranges from 11 to 13 years. The schools and the children were selected using a multistage random sampling technique. The Correlation co-efficient indicated that externalizing behavior in children and mother psychological well-being were significantly positively correlated. Results also showed that somatic symptoms, anxiety and insomnia, social dysfunction, and severe depression of mothers were significantly correlated with externalizing behavior of children. Multiple regression analysis results showed that mothers' anxiety and insomnia alone accounted for 46.9% of the variation and was the most powerful predictor of externalizing behavior. The other significant predictors were severe depression, somatic symptoms, and social dysfunction. All the predictors explained jointly 56.1% of variance in externalizing behavior of children. The implications of the findings have been discussed in the light of theory and scientific evidence from the previous studies. Jagannath University Journal of Science, Volume 11, Number 1, Jun. 2024, pp. 1−12